Large-Scale Student Assessment in Nepal: Current Practices and Future Needs - Paudel , Lekh N. (Education Review Journal, 2025)
This article provides an overview of the concepts and practices of large-scale assessment in Nepal, reviewing relevant literature. It highlights the necessity of employing large-scale assessments to identify the performance of the education system through student achievement tests. The findings of this review indicate that while awareness towards the importance of large-scale student assessment is increasing among various stakeholders in Nepal, there remains significant potential for improvement in assessment practices. This includes ensuring conducive conditions, aligning assessments with the educational system, and enhancing overall assessment quality. Additionally, the article emphasizes the importance of being aware of the potential negative consequences of large-scale assessments, urging efforts to mitigate risks while maximizing their benefits for assessing and improving the education system.